Characteristics of hailstorms in the Colorado State University network, 1960-61 - Schleusener, Richard A., author; Grant, Lewis O., author; Civil Engineering Section, Colorado State University, publisher (Colorado State University. Libraries, 1961)
Hail occurrences during 1960-61 are analyzed to show the characteristics of hailstorms as observed over the Colorado State University hail network in northeastern Colorado. Paths of hailstorms and their relation to airflow are presented, with information on frequency, time, duration, size distribution, and other information derived from measurements of hail at the ground. Values of hail impact energy are presented. Hail genesis regions, subsequent paths, and echo tops were determined during 1961 with a 3.2 cm radar. Genesis regions are related to topographic features and low-level wind flow.
CER61RAS59.
October 1961.
Keywords: Hailstorms -- Colorado; Rain and rainfall -- Colorado